Informing clients of confidentiality limits and subsequent child abuse reporting decisions: the role of dissonance - Nicolai, Katherine M. (1995)
This study proposed a causal model of child abuse reporting behavior framed within cognitive dissonance theory (Festinger, 1957). It was hypothesized that the failure to provide information regarding confidentiality limits to clients would result in dissonance. Further, it was predicted that when clients subsequently disclose that they are abusing a child, clinicians' dissonance would lead to behaviors associated with decreased reporting;Two hundred and forty-eight licensed psychologists from Arkansas, Connecticut, and New Mexico responded to a survey addressing the provision of confidentiality information in therapy and child abuse reporting decisions. Each respondent received a survey containing one of four vignette conditions describing a situation in which an adult client discloses information indicative of child abuse. The manipulated variables in the vignettes were severity of abuse (high and low) and provision of information regarding confidentiality limits (inform/no inform). In addition to describing their own practices in regard to informing clients of confidentiality limits, respondents rated the extent to which they might experience discomfort or dissonance (measured by a multi-item scale), how likely they would be to report the situation presented in the vignette, and how comfortable they would be with their reporting decision in the shoes of the clinician in the vignette. Other items assessed respondents' perceptions of the need for agency intervention in the case, and the effects that reporting the case might have on the client's treatment and on the safety of the child;Path analyses of the proposed model of reporting behavior revealed that the models did not fit the data very well overall. Failure to inform clients of limits was not directly related to decreased reporting. Additionally, hypothesized differences between conditions depicting high and low severity abuse were not supported. However, results supported the relationship between the failure to inform clients of confidentiality limits and dissonance. Further, the relation of dissonance to the belief that agency intervention could adversely affect the client's treatment was supported. Implications of the findings for practitioners, as well as for future research in the area of abuse reporting decisions and, were explored